Answer: Correct Answer is X 4/21
Step-by-step explanation: I got it right
Answer:
4/7
Step-by-step explanation:
apiece. The owner wants each package to include 50 baskets total, and he
wants to sell each package for $566. How many baskets of apples and how
many baskets of peaches should he put in each package?
A. 10 apples, 13 peaches
B. 13 apples, 10 peaches
C. 28 apples, 22 peaches
D. 22 apples, 28 peaches
Answer:
28 apples and 22 peaches
Step-by-step explanation:
<3
Answer:
3/4
Step-by-step explanation:
Answer:
3/4
Step-by-step explanation:
both the numerator and denominator can be divided by 2
6/2=3
8/2=4
so 6/8 in lowest terms is 3/4
Based on the available information, the expression (3m² + 2mn - n²) + (m² + 4mn - n²) is equivalent to 4m² + 6mn - 2n².
To simplify the expression (3m² + 2mn - n²) + (m² + 4mn - n²), we can combine like terms.
Like terms have the same variables and the same exponents.
Let's group the like terms together:
(3m² + m²) + (2mn + 4mn) + (-n²- n²)
Combining like terms within each group, we get:
4m² + 6mn - 2n²
Therefore, in this case, it is concluded that the expression (3m² + 2mn - n²) + (m² + 4mn - n²) is equivalent to 4m² + 6mn - 2n².
Learn more about Equivalent Expression here: brainly.com/question/2972832
#SPJ3
Answer:
Step-by-step explanation:
Answer:
5x^2+5x-1
Step-by-step explanation:
-2x^2+9x-3+7x^2-4x+2=5x^2+5x-1
34 ft
The perimeter of the rectangle is:
P = 136ft
For a rectangle of length L and width W the perimeter is:
P = 2*(L + W)
And for a square of side length S, the perimeter is:
P' = 4*L
The length of the rectangle is:
L = 34ft + x
The width is W = x
For the square we have the side length S = x
Here we know that the perimeter of the rectangle is twice the perimeter of the square, then:
2*(W + L) = 2*(4*S)
Replacing these variables in terms of x, we get.
2*(x + 34ft + x) = 2*(4*x)
4x + 68ft = 8x
68ft = 8x - 4x = 4x
68ft/4 = x = 17ft
Then the perimeter of the rectangle is:
P = 2*(34ft + 17ft + 17ft) = 136ft
If you want to learn more about perimeters:
#SPJ1
Answer:
0
Step-by-step explanation:
(x + y)-(x + y)
Answer:
0
Step-by-step explanation:
What is a simplified expression for (x + y)-(x + y)?